A Review of Bride Trafficking in India. Issue 2 (December 2020) - Irshad, Mohd
Human trafficking is a global phenomenon that affects people of all ages, races, gender and ethnicities. Bride trafficking is one of the worst forms of human trafficking. Many other social evils such as child marriage, domestic violence, bonded labour and prostitution are linked to bride trafficking. Bride trafficking is rampant in India since eons. Hence, there is a need to understand the underlying causes, consequences, effects and repercussions. This article explores the phenomena of bride trafficking within the larger framework of human trafficking and the available legal provisions to address it.